2003
DOI: 10.1007/bf03179920
|View full text |Cite
|
Sign up to set email alerts
|

Psyllium fibre and the metabolic control of obese children and adolescents

Abstract: In children and adolescents from developed countries, obesity prevalence has strongly increased in the last decades and insulin resistance and impaired glucose tolerance are frequently observed. Some dietary components such as low glycemic index foods and dietary fibre could be used in order to improve glucose homeostasis in these children. Psyllium or ispaghula husk (the husk of the seeds of Plantago ovata) is a mixture of neutral and acid polysaccharides containing galacturonic acid with a ratio of soluble/i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 42 publications
2
32
0
1
Order By: Relevance
“…Previous studies have also indicated that this type of fibre has no effect on HDL-C or TAG concentrations when included in a diet low in saturated fat (9,10) . In accordance with the literature, the results of the present study showed that the …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have also indicated that this type of fibre has no effect on HDL-C or TAG concentrations when included in a diet low in saturated fat (9,10) . In accordance with the literature, the results of the present study showed that the …”
Section: Discussionmentioning
confidence: 99%
“…Although there is difficulty in obtaining a representative sample of hypercholesterolaemic children for an interventional study, especially in Brazil, all the published studies on this subject have used sample sizes that are similar to or smaller than that used in the present study. Most of the randomised controlled trials that have investigated the effect of psyllium on cholesterol concentrations in children (9) have used the NCEP Step 1 diet (4) . In the present study, by contrast, this diet was used for assessing the eligibility of participants and only those with LDL-C concentrations .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This gel may hinder the access of glucose to the absorptive epithelium of the small intestine, thereby blunting postprandial glucose peaks [69]. In addition, soluble fiber may delay gastric emptying, thus slowing carbohydrate uptake [70].…”
Section: Blood Sugar Levels and Insulin Regulationmentioning
confidence: 99%
“…Plants such as Cissus quadrangularis, Aralia mandshurica, Kochujang and psyllium showed a reduction in triglycerides and cholesterol levels in serum (Abidov et al, 2006;Ahn et al, 2006;Moreno et al, 2003;Oben et al, 2007).…”
Section: Natural Products: Phytochemicalsmentioning
confidence: 99%